UNSUR PEWAYANGAN CERITA MAHABARATA VERSI NANO RIANTIARNO DALAM NOVEL WISANGGENI SANG BURONAN KARYA SENO GUMIRA AJIDARMA: KAJIAN INTERTEKSTUAL - Muhammad Agung Wibisono; Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2018)
This research aims to describe the structure of Mahabarata story version of Nano Riantiarno and novel Wisanggeni Sang Buronan by Seno Gumira Ajidarma to find the similarities and differences as well as teh intetertextual relationship of the two stories. This type of research is qualitative research. Data collection techniques are done by reading, identifying, and recording all the identifications contained in the two stories. The technique of data analysis using qualitative descriptive analysis obtained by recording and identification then the result is explained by referring to intertxtual theory. The results can be concluded that there are similarities and differences that form the basis of the story of Mahabarata and the novel Wisanggeni Sang Buronan. Novel Wisanggeni Sang Buronan has an intertextual relationship from Mahabarata story especially Wisanggeni figure in term of plot, character, and background which both share the bird of the figure of Wisanggeni. The story of Mahabarata especially the Wisanggeni figure became the hypogram of the creation of the novel Wisanggeni Sang Buronan by concreting the puppet element especially the Wisanggeni character in the Mahabarata story. Â